Persepsi Perempuan yang Menunda Pernikahan untuk Menempuh Pendidikan yang LebihTinggi - iftahatul Khoiroh; Muhammad Naharudin Arsyad (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
This study aims to analyze the perceptions of women who postpone marriage to pursue higher education. This research uses a type of qualitative method with a descriptive approach. The data collection methods in this study are observation, interviews and documentation. The results in this study are that women delay marriage because of education because higher education helps open the human mind, and with higher education will get a higher career as well.